Female high school students' knowledge and attitude toward breast cancer - Zahra Mohebi; Maryam Heidari Sarvestani; Zahra Moradi; Mohammad Mehdi Naghizadeh (BMC, 2023)
Abstract Background Breast cancer is the most common cancer among women. Even though early detection and diagnosis of this disease can reduce mortality considerably, several studies have shown that more than 92% of women are unaware of the risk factors for breast cancer and of breast cancer screening tests. The simultaneous promotion of screening and provision of education can increase community health and reduce medical costs, and students can play a leading role in informing and educating people in society. Aim The present study aims to examine the level of knowledge and attitude of female students in senior high schools in Fasa regarding breast cancer screening. Methods In this cross-sectional study, the random sampling method was applied to survey 350 female high school students, only 311 of whom completed the study. Questionnaires were completed in girls' high schools, and the data was analyzed by SPSS Software, Version 25. Results The results revealed that more than 87% of students were unaware or had incorrect information regarding breast cancer screening. The link between the type of breast cancer information sources and students' general knowledge was significant. Most students were aware of the risk of breast cancer, but they were uninformed of its symptoms, risk factors, and prevention strategies, and students with a family history of breast cancer had a higher score in terms of mammography knowledge than students with no family history of breast cancer, although this difference was not significant (mean ± standard deviation = 0.94 ± 0.90 vs. 0.67 ± 0.81, p = 0.19). Conclusion The level of awareness and attitude of Fasa high school girls regarding breast cancer and screening methods is not acceptable. Therefore, it is recommended that educational programs be implemented to increase the awareness of students in schools, so that the number of screenings increases with the institutionalization of this information. Likewise, by transferring information through students to their families, the level of awareness in the whole society will hopefully increase as well.